Remarking the Silence: Prayer after the Death of God - Sanders, Theresa (Horizons, 1998)
The critique of ontotheology undertaken by Heidegger and expended by Derrida calls into question not only the meaning but the possibility of God-language. In response, thinkers such as Kevin Hart have attempted to map out an area of non-metaphysical theology that draws on the resources of negative theology. Hart's work, The Trepass of the Sign, however, contains three significant ambiguities. First, he defines negative theology as a denial that God can be described using predicates, but in his text negative theology has a quasi-positive (rather than merely negative) role. Second, Hart contends that negative theology precedes positive theology, but in fact it seems to depend upon a prior affirmation of God. Third, Hart offers no rationale for negative theologians' use of the word "God." Derrida writes that the only way out of negative theology's referential vacuity is prayer: which, he continues, mires that theology in metaphysics. However, if prayer is understood as agape rather than knowledge or supplication, a way through Hart's ambiguities might be found.